Succeeding as a therapist : how to create a thriving practice in a changing world - Adames, Hector Y.; Chavez-Dueñas, Nayeli Y.; Vasquez, Melba Jean Trinidad; Pope, Kenneth S. (American Psychological Association, 2023)
"This user-friendly, practical guide summarizes everything therapists need to know about setting up, growing, and protecting their independent therapy practice. The chapters flow from creating a business plan and start-up to closing or selling a practice, and cover everything in between, like helping clients find you, preparing for emergencies, self and community care, and legal, insurance, and financial issues. Also included are key professional and legal guidelines. "--